Correlation Between Oral Contraceptives Use and Sexual Activity with Cervical Cancer - Vita Wulandari (Universitas Airlangga, 2016)
The World Health Organization in 2012 showed that of the total new cases of cervical cancer in the world, 85% of cases were found in developing countries. In 2015, Malang City and Malang District were alert for cervical cancer. This study aims to analyze the relationship between risk factors for use of oral contraceptives and sexual activity with the incidence of cervical cancer in patients in the Obstetrics and Gynecology Clinic of the Regional Public Hospital (RSUD) Dr. Saiful Anwar Malang. This study uses a case-control design. The study population was poly obstetrics and gynecology outpatients Dr. Saiful Anwar Malang in November 2015. Case samples were 37 cervical cancer patients and 111 control samples were non-cervical cancer patients. Sampling using systematic random sampling. Data analysis using the Chi-square test. The independent variables studied were the use of oral contraceptives and sexual activity which included the age of first sexual intercourse <18 years, the age of first pregnancy <18 years, and a history of abortion. Primary data collection uses interviews while secondary uses the patient's medical record. The results showed there was a relationship between the age of first sexual intercourse <18 years (p = 0.0225147014; OR = 2.3194; 95% CI = 1.0854–4.9561), age of first pregnancy <18 years (p = 0.0236276656; OR = 2.33388; 95% CI 1.0890-5.0230), and history of abortion (p = 0.0038911219; OR = 3.2653; 95% CI = 1.4593–7.3063) with cervical cancer. The conclusion of this study is the age of first sexual intercourse, age at first pregnancy and abortion are risk factors for cervical cancer.